Perceptions regarding team-based learning among undergraduate physical therapy students - Muhammad Furqan Yaqoob; Zara Khalid; Muhammad Ehab Azim; Sana Ahsan; Muhammad Furqan Hassan; Aamer Naeem (Journal of the Pakistan Medical Association, 2020)
Team-based learning (TBL) is a strategy where teams work together to develop concepts and apply them towards problem-solving. This latest learning approach has not been tried in the educational environment of Rehabilitation Sciences. Hence, this study aimed to assess the knowledge and practices regarding TBL among undergraduate physical therapy students. A descriptive cross sectional survey was conducted involving 222 undergraduate physical therapy students who were selected via non-probability convenience sampling from Foundation University Institute of Rehabilitation Sciences over a period of three months (May 2018 - July 2018). Data was collected using questionnaire in the light of literature review, developed by Wright States University’s Department of Communication based on the Minnesota satisfaction questionnaire. It contained questions regarding knowledge, practices and satisfaction with team-based learning, assessed via 19 statements on 5-point Likert scale. Continuous....